Nutrition and essential and non-essential compounds in epigenetic degradation associated with preventing and fighting cancer (Research, Society and Development, 2022)
The components present in some foods have the ability to directly influence the health-disease process through epigenetic molecular mechanisms, reducing the risk of developing some diseases, especially Chronic Noncommunicable Diseases (NCDs), such as cancer. In this sense, the present study seeks to elucidate the role of some nutrients and bioactive compounds in food in epigenetic modulation as a way of preventing and fighting cancer. Therefore, a scope review was carried out in the LILACS, PubMed and VHL databases. The following descriptors were used: Epigenomics, Phytochemical Compounds, Neoplasms and Nutrients, all selected according to the Health Sciences Descriptors and used in Portuguese and English. Initially, 647 publications were found and after the application of the pre-defined inclusion and exclusion criteria, 9 relevant publications remained for the construction of the work. From the selected literature, it was found that some nutrients and bioactive compounds, such as Curcumin from turmeric, Sulforaphane and Phenethyl Isothiocyanate (PEITC) from cruciferous vegetables, Resveratrol (RES) from red grapes and wine , β-carotene from orange vegetables, Vitamin C from citrus fruits and some phytochemicals, such as Quercetin and Caffeic acid, play an important role in the fight against cancer, because, among other benefits, they can epigenetically stimulate the gene expression of factors preventive measures, but can also inhibit the expression of factors linked to metastasis and progression of the pathology already installed. Finally, it is clear that the influence that some foods have on gene expression represents an important tool against cancer, especially in relation to prevention. However, it is necessary to carry out more detailed studies in relation to doses and possible harmful effects.